Striking a balance: Managing El Niño and La Niña in Lao PDR’s agriculture - Sutton, William R.; Srivastava, Jitendra P.; Rosegrant, Mark W.; Koo, Jawoo; Robertson, Richard D. (World Bank, 2019)
This report’s purpose is to help Lao policy makers and stakeholders prepare for future El Niño–Southern Oscillation (ENSO) events. It does this by providing information on ENSO’s poverty, economic, and agricultural impacts in Lao PDR and outlining ways forward. The report finds that ENSO’s impacts vary from region to region and harm Lao PDR’s people, economy, and agricultural sector. The country has sought to prepare for climate risks through climate change adaptation and disaster risk management but could do more to prepare specifically for ENSO events. Preparing for ENSO is important because of Lao PDR’s exposure to ENSO-related climate shocks, the importance of agriculture in the national economy, the rural population’s climate and economic vulnerability, and the lack of research on ENSO in Lao PDR.This report is timely given the lack of research on ENSO in Lao PDR and the high likelihood the country will face another El Niño in the near term. It is difficult to disentangle ENSO’s impacts from those of other climate shocks, natural disasters,and economic cycles. This makes it more difficult to design policies and response mechanisms that help mitigate ENSO-related welfare losses and economic damages.This report evaluates El Niño and La Niña’s impacts on Lao PDR’s agricultural sector particularly crops, livestock, and fisheries—and how these have implications for the economy and society. It then looks at the actions undertaken by the Lao government to mitigate the losses associated with climate risks. This includes actions to prepare and respond to climate change and natural disasters. Next, the report simulates how well certain policy options mitigate ENSO-related GDP and welfare losses. It concludes by recommending actions to enhance Lao PDR’s preparedness for future ENSO events.